2023
DOI: 10.3389/fspor.2022.1055302
|View full text |Cite
|
Sign up to set email alerts
|

Ground reaction force and electromyograms of lower limb muscles during fast walking

Abstract: BackgroundPhysically active status is an important contributor to individual health. Walking is regarded as commonly accepted exercise for exercise promotion. Particularly, interval fast walking (FW), consisting of alternating between fast and slow walking speeds, has gained popularity from practical viewpoints. Although previous studies have determined the short- and long-term effects of FW programs on endurance capacity and cardiovascular variables, factors affecting these outcomes have not been clarified. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Similarly, some studies have confirmed that the RFD is indicated by the slope of the force-time curve. The lower limbs could exert a greater force in a shorter period of time, which also shows that the number of muscle fibers determines the amount of force generated [45][46][47]. Some studies have pointed out that an excellent vertical jump is dominated by the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some studies have confirmed that the RFD is indicated by the slope of the force-time curve. The lower limbs could exert a greater force in a shorter period of time, which also shows that the number of muscle fibers determines the amount of force generated [45][46][47]. Some studies have pointed out that an excellent vertical jump is dominated by the hip joint.…”
Section: Discussionmentioning
confidence: 99%